Development of a Staggered PCD End Mill for Carbon Fiber Reinforced Plastic - Guangjun Liu; Xin Qian; Hongyuan Chen; Fei Gao; Tao Chen (Applied Sciences, 2017)
This work presents a PCD (polycrystalline diamond) end mill with a new staggered structure for the milling of CFRP (carbon fiber reinforced plastic). The magnitude and direction of cutting force is decreased and changed by side-edge re-configuration of the structure. The flute and insert pocket of the staggered PCD end mill are designed considering the tool’s stiffness and welding process. The milling process and machining defects of the staggered PCD end mill are analyzed, and the structural parameters of the staggered PCD end mill are determined. The staggered PCD end mill is fabricated by the process of wire cutting, NC (Numerical Control) machining, high-frequency induction brazing, welding, grinding and passivation. Milling tests of multidirectional CFRP with the staggered PCD end mill is conducted on CNC (Computerized Numerical Control) milling machine. The milling force is measured by a dynamometer. A range analysis of the numerical results of milling force is conducted after milling test, and the influence of milling parameters on milling force is analyzed. A regression model of the milling force is built and verified by experiment. The effects of fiber cutting angle on milling force are obtained through milling CFRP with different fiber orientation angles.